Perancangan Arsitektur Interior Kantor PT. Conbloc Indotama Surya di Surabaya - Cynthia Valencia; Astrid Kusumowidagdo; Stephanus Evert Indrawan (Universitas Ciputra Surabaya, 2016)
PT. Conbloc Indotama Surya is a company that works as a producer of concrete paving. The office is located at the 2nd floor Sentra Niaga Utama, Kota Mandiri Citra Raya. Physical building is a commercial office, and the area designed at the 2nd floor. In offices, comforts and effectiveness in activities is an important element that must be considered. In addition, it is good if a company is able to support their own values. Through observation and study of the literature, finally able to find a solution in the form of application of the values of PT. Conbloc Indotama Surya, and the psychology of color, as well as a modern interior style. In providing the solutions, presented by the interior design in terms of layout, content of the room, and ergonomics.